Last updated at Dec. 8, 2016 by Teachoo
Transcript
Example 20, Find the sum to n terms of the series whose nth term is n (n+3). Given an = n (n + 3) = n2 + 3n The sum of n terms is = (n( n + 1)(2n + 1))/6 + (3n( n + 1) )/2 = (n(n + 1))/2 (( (2n + 1))/3 " + 3" ) = (n(n + 1))/2 (( (2n + 1) + 9)/3) = (n(n+1))/2 × (( 2𝑛 +10 )/3) = (n(n+1))/2 × ( 2(𝑛 +5) )/3 = (n( n + 1)(n + 5) )/3 Thus, the required sum is (n( n + 1)(n + 5) )/3
Examples
Example 1 (ii)
Example 2
Example 3 Important
Example 4
Example 5
Example 6 Important
Example 7
Example 8 Important
Example 9
Example 10 Important
Example 11
Example 12 Important
Example 13
Example 14 Important
Example 15 Important
Example 16
Example 17 Important
Example 18 Important
Example 19 Important Deleted for CBSE Board 2022 Exams
Example 20 Deleted for CBSE Board 2022 Exams You are here
Example 21 Important
Example 22
Example 23
Example 24 Important
Examples
About the Author